E-Modul Flipbook sebagai Sumber Pembelajaran Akuntansi pada Sekolah Menengah Kejuruan - Siti Julaeha; Endang Herawan; Aan Anisah (Universitas Negeri Padang, 2023)
This research aims to as produce a design for teaching materials of the type of e-module in the form of a flipbook. The approach in this study is a qualitative approach with a design-based research (DBR) method. This research produces flipbook e-module teaching materials made using a corporate flip PDF application that can be accessed on the web on various devices. Based on the validation results, this flipbook e-module is categorized as very feasible with an average overall score of the three is 3,81 so that this flipbook e-module is suitable for use as teaching materials in vocational high schools.